Effect of different antioxidants on properties of trans-1,4-butadiene-isoprene rubber and its composites - ZONG Xin1,2, GAO Bo1,2, LI Lan-ge1,2, GE Huai-tao1,2, LI Dan-dan2 (Hecheng xiangjiao gongye)
The effects of three antioxidants on aging properties of raw trans-1,4-poly(butadiene-co-isoprene) copolymer rubber (TBIR), curing characteristics of natural rubber (NR)/TBIR rubber compounds, and physical and mechanical properties and flexural fatigue resistance of NR/TBIR vulcanizates were studied. The results showed that different types of antioxidants had different anti-aging effects on raw TBIR and NR/TBIR composites. The oxidation induction temperature and oxidation induction time of raw TBIR containing different antioxidants were different, and the oxidation induction temperature was the highest of raw TBIR containing hindered phenolic, p-phenylenediamine and phosphite composite antioxidant and the oxidation induction time was the longest, and the thermal-oxidative aging resistance was the best. Compared with NR compound, the minimum torque of different NR/TBIR compounds all increased to varying degrees, the scorch time were prolonged, the vulcanization time were shor-tened and the vulcanization rate were accelerated, and the vulcanization rate of the compound contai-ning composite antioxidant was faster than that of the other NR/TBIR compounds. The types of antioxidants had no significant effect on the physical and mechanical properties and room-temperature flexural fatigue resistance of NR/TBIR vulcanizates. Compared with the NR vulcanizate, the tensile strength, modulus, and elongation at break of the NR/TBIR vulcanizates were slightly lower, the abrasion resistance was significantly improved, while the rolling resistance was significantly reduced; compared with NR vulcanizate, except for NR/TBIR vulcanizate containing hindered phenolic antioxidant, the aging coefficients of the other vulcanizates all reduced; compared with NR vulcanizate, the room temperature fatigue life of NR/TBIR vulcanizates were significantly prolonged and the high-temperature fatigue life at 90 ℃ all extended to varying degrees, and the vulcanizate containing only hindered phenolic antioxidant had the longest fatigue life; after aging at 100 ℃ for 48 h, the grade 6 fatigue life of NR/TBIR vulcanizate containing only hindered phenolic antioxidant was significantly prolonged, while the fatigue life of the other NR/TBIR vulcanizates and NR vulcanizate remained basically unchanged. Overall, hindered phenolic antioxidant had a good thermal-oxidative aging protection effect on NR/TBIR vulcanizate.